Maintaining Local Wisdom - Building a Harmonious Life: Inter-Ethnic Relations in Paya Itik Village, Galang District, Deli Serdang Regency - Junita Setiana Ginting; Edi Sumarno; Nina Karina; M. Azis Rizky Lubis (Budapest International Research and Critics University, 2020)
Diversity in people's lives is a reality that must be accepted. This diversity can take the form of religious diversity, ethnic diversity, and racial diversity. Each of these forms of diversity has a culture that is formed within the community, be it religion, ethnicity or race. The culture that is owned by each religion, ethnicity, and race is what society then practices in everyday life. Of course this is not an easy matter, because every group of people who carry this culture tends to stick to what they believe, without respecting the beliefs carried by others. However, this could be overlooked if the existing boundaries of diversity can be handled wisely. This is what is then seen in the community in Paya Itik Village, Galang District, Deli Serdang Regency, which consists of ethnic Banjar, ethnic Karo, and ethnic Javanese. Community relations in the village are harmonious. This harmony is established thanks to the local wisdom that grows in the community. This paper discusses how village communities build a harmonious life by maintaining local wisdom. The discussion starts from the social life of the community, religious life and community culture, and